On generalized ideal asymptotically statistical equivalent of order α for functions - Öztürk, M.; Savaş, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce new definitions related to the notions of asymptotically I_λ -statistical equivalent of order α to multiple L and strongly I_λ -asymptotically equivalent of order α to multiple L by using two nonnegative real-valued Lebesque measurable functions in the interval (1,∞ ) instead of sequences. In addition, we also present some inclusion theorems.